Skeletal Muscle and the Effects of Ammonia Toxicity in Fish, Mammalian, and Avian Species: A Comparative Review Based on Molecular Research - Miramontes, Emily; Mozdziak, Paul; Petitte, James N; Kulus, Magdalena; Wieczorkiewicz, Maria; Kempisty, Bartosz (International journal of molecular sciences, 2020)
Typically, mammalian and avian models have been used to examine the effects of ammonia on skeletal muscle. Hyperammonemia causes sarcopenia or muscle wasting, in mammals and has been linked to sarcopenia in liver disease patients. Avian models of skeletal muscle have responded positively to hyperammonemia, differing from the mammalian response. Fish skeletal muscle has not been examined as extensively as mammalian and avian muscle. Fish skeletal muscle shares similarities with avian and mammalian muscle but has notable differences in growth, fiber distribution, and response to the environment. The wide array of body sizes and locomotion needs of fish also leads to greater diversity in muscle fiber distribution and growth between different fish species. The response of fish muscle to high levels of ammonia is important for aquaculture and quality food production but has not been extensively studied to date. Understanding the differences between fish, mammalian and avian species' myogenic response to hyperammonemia could lead to new therapies for muscle wasting due to a greater understanding of the mechanisms behind skeletal muscle regulation and how ammonia effects these mechanisms. This paper provides an overview of fish skeletal muscle and ammonia excretion and toxicity in fish, as well as a comparison to avian and mammalian species.
Keywords: Animals; kosterní svaly; Mammals; Ammonia; hyperamonemie; Birds; Liver Cirrhosis; Hyperammonemia; Muscular Atrophy; jaterní cirhóza; Fishes; svalová atrofie; myostatin; Muscle, Skeletal; ryby; ptáci; kosterní svalová vlákna; mammal; ammonia; avian; savci; Muscle Fibers, Skeletal; vývoj svalů; fish; zvířata; sarkopenie; amoniak; Muscle Development; Sarcopenia; muscle